Clouston syndrome with palmoplantar keratoderma - M P Singh; Manishi Singh; Manika Singh; Prashant Tripathi (Wolters Kluwer Medknow Publications, 2011)
Clouston syndrome (hidrotic ectodermal dysplasia) is characterized by the clinical triad of nail dystrophy, alopecia and palmoplantar hyperkeratosis. Clouston syndrome is transmitted as an autosomal dominant trait and caused by mutations in the GJB6 gene (13g12), encoding the gap junction protein connexin 30 (C x 30). At present, there is no treatment for the disease and management is purely supportive. The life of span, patients is normal. In this report, a case of 9-year-old boy is presented who had few set of primary dentition, but surprisingly complete absence of permanent dentition which observed radiographically. In this case, anodonfa of permanent dentition was present and no alopecia which is a rare finding.